Organ donation: Key factors influencing the younger generation's decision-making in China - Chen, Xiulan; Wei, Wei; Ai, Weili (Frontiers in Public Health, 2023)
Background The organ transplantation sector in China is facing a severe shortage of donors, and the organ donation rate needs to be increased. Since 2015, voluntary donation by citizens has become the only source of organs for transplantation in China. In recent years, there has been a relatively positive change in young people's attitudes toward organ donation after death. The aim of the study was to understand young people's perceptions and attitudes toward organ donation and the factors that influence them and can positively impact the promotion of organ donation. Methods By analyzing relevant literature and legal texts, we developed a questionnaire. Information was obtained through questionnaires and interviews, and 501 valid questionnaires were returned from the target group. A chi-square test was used to examine whether there were significant differences in the willingness to organ donation among young people with different characteristics. A factor analysis was used to investigate the main factors influencing the different attitudes of young people toward organ donation, and a one-way ANOVA was used to examine whether young people with different characteristics were affected differently by different factors. Results In our survey of young people aged 18–30 years, 99.2% of respondents knew about organ donation, 47.1% were willing to donate organs, and 15.2% understood that there were corresponding laws and regulations for organ donation. The study's findings showed that urban residents are more willing to be organ donators than rural residents; people with higher education levels have better awareness and are more willing to donate an organ; and people with religious beliefs are more likely to donate organs. The main factors that support the willingness of young people to donate are the social environment that provides support, their optimism in dealing with death, and their desire to realize their final value after death. The main factors for those unwilling to donate were low awareness or misconceptions about organ donation among individuals and their families and their attitudes toward death. As the people who took the questionnaire are probably interested in organ donation, the sample results will show a higher percentage of people who know about organ donation. We hope to discuss further with a larger and broader sample coverage to improve the estimates' validity and reflect the overall picture more accurately in a future study. Conclusion Young people knew about organ donation but had a low depth of awareness. Household registration type, education level, and religious affiliation significantly correlate with people's willingness to donate. The supportive environment for organ donation in society and the correct understanding of the organ donation process and laws and regulations can influence people's willingness to donate.